Gender and racial/ethnic differences in adolescent intentions and willingness to smoke cigarettes: Evaluation of a structural equation model. (March 2021) - Epperson, Anna E; Wallander, Jan L; Song, Anna V; Depaoli, Sarah; Peskin, Melissa F; Elliott, Marc N; Schuster, Mark A
Dual-process theories may be effective at predicting adolescent smoking; however, little is known about the effectiveness of these models across race/ethnicity and gender. Adolescents ( N = 4035) completed biopsychosocial and tobacco-related perception measures in Grade 7 and reported on smoking initiation in Grade 10. Using structural equation modeling and comparing models by gender and race/ethnicity showed differences, where both intentions and willingness predicted smoking initiation for only Black and male adolescents, compared to their Latino and White and female counterparts. Intentions and willingness appear to play a role in whether an adolescent will initiate smoking in the future, but this does not apply universally across gender and race/ethnicity.